Diversity patterns of selected predaceous arthropod groups in maize fields and margins in South African Highveld grassland. (10th January 2018) - Botha, Monique; Siebert, Stefan J.; van den Berg, Johnnie; Ellis, Suria; Greyvenstein, Bianca M.
Abstract: Conservation biological control focuses on enhancing arthropod predator habitats by increasing the natural resources required for survival and reproduction. However, this requires knowledge about the specific requirements of these predators, which can only be acquired from species‐level data. We provide a description of species‐level diversity patterns of the arthropod predator groups Araneae, Coccinellidae, Mantodea and Neuroptera from maize agro‐ecosystems in South Africa. Predators were sampled by sweep‐net at regional and local scales within the Dry Highveld Grassland Bioregion. A list is provided of predators that occurred naturally inside maize agro‐ecosystems, which may be good candidates for the biological control of pests. Diversity indices displayed significantly lower values in maize fields compared with uncultivated vegetation. Marginal and rangeland vegetation had similar diversity levels. Predator diversity of maize was probably dependent on source populations from uncultivated vegetation, highlighting the importance of field margins with respect to maintaining predator diversity in pest management regimes for maize fields. Some predators frequented maize fields, suggesting adaptability to agricultural disturbance. Generalists including Cheilomenes lunata, Chrysoperla congrua and Enoplognatha molesta may be suitable for conservation biocontrol because they can persist in annual agro‐ecosystems year‐round provided that they have access to field margins.